A pocket for Corduroy : story and pictures - Freeman, Don, 1908-1978. (New York : Viking Press, 1978)
A toy bear who wants a pocket for himself searches for one in a laundromat.
Keywords: Toys -- Fiction; Pockets -- Fiction